Pharmacological mechanism of a drug pair of astragali and cinnamon in shiquan dabu decoction - Yan, Hui; Jiang, Mingzhu; Wu, Qiongying; Gui, Zhongzheng (Bangladesh Journal of Pharmacology, 2011)
The pharmacological mechanism of drug pair of astragali and cinnamon in shiquan dabu decoction were studied in blood deficiency and Qi deficiency modeled mice. In Qi deficiency, the drug pair of astragali and cinnamon in shiquan dabu decoction had the ability of improving the number of white blood cells and peyer patches, and T cell activity. It had no action in red blood cell number and phagocytic activity of peritoneal macrophage, and B cell activity. In blood deficiency, the drug pair of astragali and cinnamon in shiquan dabu decoction had the effect of improving the hemoglobin content and T cell activity. It did not affect the number of white blood cells and peyer patches, phagocytic activity of peritoneal macrophage and B cell activity. In conclusion, the drug pair of astragali and cinnamon in shiquan dabu decoction has different actions, the quantity of drug pair in shiquan decoction should be changed according to the symptoms in process of diseases.